Spooky tricks - Wyler, Rose; Ames, Gerald; Schindler, S. D. (New York : Scholastic Inc., 1998)
Describes how to write invisible messages, make ghosts appear on walls and many other tricks.
Previously published: New York : HarperTrophy, 1994.
Text originally published: New York : Harper & Rowe, 1968.
108118
Keywords: Magic tricks -- Juvenile literature; Juvenile works